Wild edible plants of the Yao people in Jianghua, China: plant-associated traditional knowledge and practice vital for food security and ecosystem service - Qiong Fang; Zhuo Cheng; Ruifei Zhang; Binsheng Luo; Chunlin Long (BMC, 2024)
Abstract Background Traditional ecological knowledge (TEK) and practice associated with wild edible plants (WEPs) is an important part of local culture of the Yao people in Jianghua Yao Autonomous County, which possesses the biggest population of Yao ethnic group in China. Economic development, urbanization, and transition of lifestyle and changing interests of the younger generations risk loss of such valuable knowledge. However, no record had been reported about WEPs from the Yao communities of Jianghua County. It is urgent to assemble data on the major WEPs and their uses in Jianghua. This can be used to educate and stimulate new interest in these WEPs, to aid inheritance and improvement of cultural identity and confidence, to enhance local resilience to various changes and to suggest pathways for novel and value-added applications to create new local business opportunities. Methods To record WEPs associated with TEK and practice, we conducted field surveys in 2018, 2019 and 2023. The ethnobotanical methods such as free-listing, participatory observation, semi-structured interview, and market survey were adopted in the field investigations. Information about WEPs including vernacular names, parts used, ways of use, and collection time were recorded. Voucher specimens were collected, identified, and deposited in the herbarium at Minzu University of China, in Beijing. Results Totally, 81 Yao people from 12 villages were interviewed. WEPs traditionally play a crucial role in Yao peoples' daily lives. A total of 130 plant species from 89 genera and 49 families were recorded. The plants collected showed great diversity and reflected unique local culture. Most (54.5%) WEPs were also used as medicines. Baba can be defined as a cultural identity food, and WEPs are commonly used as tea substitutes for their health benefits. Conclusions We conclude that WEPs use is facing great challenges in a rapidly changing era. Preservation of WEPs related practice and knowledge is not only important for conserving local biocultural diversity, but also valuable in providing potential functional and healthy materials for food security and future economic development. Cultivation of young generations' interest in nature and biodiversity, combined with local policy to enhance public awareness are recommended.